ANALISIS KEMAMPUAN PEMAHAMAN DAN PEMECAHAM MASALAH MATEMATIK SISWA MTs PADA MATERI BANGUN RUANG SISI DATAR - Sari, Kusnita Damar; Rismayanti, Rismayanti; Puspitasari, Indah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
Mathematical cognitive abilities that must be possessed by students one of them is the ability to understand mathematics and mathematical poblem solving. The pupose of this study is to determine the extent to which the ability and solving mathematical problems that students have. The research method used is qualitatve descriptive with sampel nineteen students class IX MTs in Cianjur egency. The test instrument was given five questions of mathematical comprehension and five problems of mathematical problem solving test. Based on the results of ability to comprehend and solve mathematical problems, the understanding and problem solving skills of MTs students in Cianjur regency is still low.